A Study Of The Impact Of The Regulatory Framework And Bank's Initiatives On The Adoption Of Internet Banking In Malaysia - Perera, Corinne Jacqueline (2003)
This study is to examine the impact of regulatory framework and banks initiatives on the adoption of Internet Banking in Malaysia.